입자영상유속계를 이용한 대형수송함(LPH) 갑판 상부의 유동장 측정 연구 - 심호준; 정진덕; 조태환; 이승훈; 송지수; Shim, Hojoon; Chung, Jindeog; Cho, Taehwan; Lee, Seunghoon; Song, Gisu (大韓造船學會 論文集, 2022)
The flow field measurement above whole area of the flight deck on 'Landing Platform Helicopter (LPH)' was performed by using PIV system in wind tunnel. In various heading angle conditions (0deg, -30deg, -45deg, -60deg, -75deg and ±90deg), the velocity fields such as U velocity & V velocity were measured at three different height above flight deck. Due to the geometrical characteristics of several bodies like deck, crane and super-structure, various vortex were generated. When the heading angle is 0deg, the deck edge vortex by flight deck and massive separation by super-structure were clearly observed by visualization with smoke and PIV, respectively. In other heading angles, the acceleration of flow in space between crane and super-structure were detected. And area with flow separation by super-structure is directly related to the heading angle of vessel.